The importance of fats in food of persons physically active - Tomasz Włodarczyk; Anna Leśków; Aleksandra Całkosińska; Małgorzata Tarnowska; Aleksander Całkosiński; Natalia Dorosz; Ireneusz Całkosiński (Journal of Education, Health and Sport, 2017)
A diet program of physically active individuals accounts for about 50% of the success in attaining the desired physical form. Patterns that include resting metabolism, physical activity, and daily energy expenditure, as needed: reduction, stabilization, weight gain, are used. Among those who practice sports for whom nutrition is of great importance in achieving their goal, recently, there has been a great deal of interest in ketogenic diets, low carbohydrates commonly called "fatty". Therefore, it is important to explain the importance, types and role of fats in the nutrition of physically active persons.